PENGUJIAN EFEKTIVITAS WAKTU PEMANGKASAN BUNGA JANTAN TERHADAP PENINGKATAN KOMPONEN HASIL DAN HASIL JAGUNG MANIS (Zea may L) - Lia Amalia (Paspalum: Jurnal Ilmiah Pertanian, 2017)
The research was conducted in experimental garden of Faculty of Agriculture Unwim which has a place to stay 850 mdpl. This study aims to determine the effective timing of male pruning to increase yield components and sweet corn yield. The environmental plan used is a collection of groups consisting of: A = Without pruning B = Pruning 7 days after pollination C = Pruning 14 days after pollinationD = Pruning 21 days after pollination. The result of the research showed that the male flower pruning after pollination of the effect on corn yield and yield components such as Weight, Length and Diameter of Tonggol both without and with kelobot. Sweet corn plants that are not exposed to male flower pruning have the same result and yield components as the plants that are trimmed by their male flowers